(untitled) (Feni University Journal, 2026)
Soft skills are essential for career success and maintaining positive social connections. Employers place high importance on these traits when employing young graduates. The primary purpose of this research is to analyze how university students value soft skills in terms of their academic and professional success. This study followed the survey method. The study population is students of Khulna University, Bangladesh. The survey was completed by 250 students from Khulna University’s undergraduate and graduate programs. In this study, all the data are collected through a questionnaire with open-ended and close-ended questions. The majority of respondents agreed that soft skills help one’s social life and one’s career. However, they did not believe these abilities significantly boosted their social interaction skills. Students ranked teamwork and collaboration, problem-solving, time management, decision-making, and a hunger for knowledge as the top five most important soft skills. This study provides several suggestions for enhancing students’ soft skills, which may increase their employability. Respondents were asked how universities could improve students’ soft skills. Over 72.4% of students supported adding curriculum-based soft skills development activities. Respondents were then asked to suggest soft skill-building strategies for students. Most respondents advised sending students to professional development classes to improve soft skills. 77.2% also advised students to attend student union-organized soft-skill development events. FENI UNIVERSITY JOURNAL, 2024, 3(1), ISSN [2518-3869], PP. (167-188)